2018
DOI: 10.15666/aeer/1601_903912
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Potentially Algicidal Effects of Thymus Satureioides Coss. And Artemisia Herba Alba L. Against Microcystis Aeruginosa

Abstract: Abstract. In search of an ecofriendly algaecide, aqueous extracts of two medicinal plants, Thymus satureioides Coss. and Artemisia herba alba L., were assessed for antialgal activity against Microcystis aeruginosa. An experiment was designed using five treatments (1%, 0.75%, 0.5%,0.25% and 0.1%). The growth of M. aeruginosa, morphological modifications, and photosynthetic pigments (chlorophyll a and carotenoids) on exposure to the extracts were explored. Also, phytochemical parameters in the extracts were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…In a recent study, Tebaa et al [ 59 ] showed that the aqueous extracts of T. satureioides aerial parts are rich in total polyphenols (285 ± 34.82 μ g gallic acid equivalent/mL aqueous extract), in total flavonoids (25.83 ± 4 μ g catechin equivalent/mL aqueous extract) and in total tannins (0.032 ± 0.002 μ g tannic acid equivalents/mL aqueous extract).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Tebaa et al [ 59 ] showed that the aqueous extracts of T. satureioides aerial parts are rich in total polyphenols (285 ± 34.82 μ g gallic acid equivalent/mL aqueous extract), in total flavonoids (25.83 ± 4 μ g catechin equivalent/mL aqueous extract) and in total tannins (0.032 ± 0.002 μ g tannic acid equivalents/mL aqueous extract).…”
Section: Resultsmentioning
confidence: 99%
“…In order to obtain pure isolates, a series of successive sub‐culturing was carried out in Z8 medium in a culture chamber under controlled conditions: light intensity of 63 micromole photon. m −2 s −1 using cool white fluorescent lamps, a light/dark photoperiod of 15:9 h and temperature of 25 ± 2°C (Tebaa et al ., 2018; Tazart et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…There are various allelochemicals, including terpenes, phenolics, aromatics, tannins, alkaloids, and flavonoids [19][20][21][22][23]. Since the allelochemicals are derived from plants, many attempts have been conducted to use the allelochemicals or extracts containing the chemicals as eco-friendly algaecides [3,24,25]. However, these attempts have focused on controlling algae rather than considering their impact on hydroponic crops.…”
Section: Introductionmentioning
confidence: 99%